Climate variability across the last deglaciation in NW Iberia and its margin. (1st September 2016) - Naughton, F.; Sanchez Goñi, M.F.; Rodrigues, T.; Salgueiro, E.; Costas, S.; Desprat, S.; Duprat, J.; Michel, E.; Rossignol, L.; Zaragosi, S.; Voelker, A.H.L.; Abrantes, F.
Abstract: The direct comparison between marine and terrestrial data from the NW Iberian margin, core MD03-2697, allows us to accurately evaluate, without chronological ambiguity, the vegetation response to North Atlantic climate events across the last deglaciation. Comparison of MD03-2697 data with other marine and terrestrial records from a vast area stretching from the Azores to western (W) France, Iberia and its margin, the W Mediterranean and NW Africa reveals the importance of enhanced winter North Atlantic westerlies episodes in driving a heterogeneous regional climatic signal during particular events of the last deglaciation. Heinrich Stadial 1 (HS1)/Oldest Dryas is a complex event marked by three synchronous main phases (a: extremely cold/relatively wet; b: cool/dry; c: relatively warmer/increasing moisture availability) in regions directly influenced by the North Atlantic while it is characterized by a single phase (cold and dry) in most inland and high altitude areas. Changes in the strength and position of North Atlantic westerlies could explain the variability in moisture during HS1 from W Pyrenees to W Mediterranean. The Bølling-Allerød (B-A) event is marked by a synchronous progressive increase of ocean and atmospheric temperatures and precipitation from the Bølling to the Allerød in W Iberia and W Pyrenees contrasting with the Greenland temperature pattern. Mid-to high latitudes thermal contrast and the gradual strengthening of the Atlantic Meridional Overturning Circulation (AMOC) triggered the continuing enhancement of westerlies, and moisture, along this period. Finally, the Younger Dryas (YD) Stadial is characterized by a land-ocean synchronous returning cold conditions (but not so cold as HS1) and, although dry conditions persisted during this period, extreme winter precipitation occurrences might have affected the most coastal areas of north and central W Iberia and Pyrenees. In contrast, dry conditions persisted during the YD in the western Mediterranean regions. The westerlies migrated further north following the displacement of the Polar Front during the deglaciation precluding the input of moisture in the W Mediterranean region, which persisted very dry during the YD Stadial.